2018
DOI: 10.1016/j.forsciint.2018.08.036
|View full text |Cite
|
Sign up to set email alerts
|

A forensic investigation on the persistence of organic gunshot residues

Abstract: Gunshot residues (GSR) are a potential form of forensic traces in firearm-related events. In most forensic laboratories, GSR analyses focus on the detection and characterisation of the inorganic components (IGSR), which are mainly particles containing mixtures of lead, barium and antimony originating from the primer. The increasing prevalence of heavy metal-free ammunition challenges the current protocols used for IGSR analysis. To provide complementary information to IGSR particles, the current study concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“…The collection of OGSR was performed with GSR stubs (Ted Pella Inc, USA). The thumb-forefinger region of the palm and back of the hand, as well as the wrist, were thoroughly sampled until the stub surface was no longer sticky [21][22][23]. Each hand was sampled using an individual stub with the collected specimens packaged separately by sealing with the cover and placed in their respective boxes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collection of OGSR was performed with GSR stubs (Ted Pella Inc, USA). The thumb-forefinger region of the palm and back of the hand, as well as the wrist, were thoroughly sampled until the stub surface was no longer sticky [21][22][23]. Each hand was sampled using an individual stub with the collected specimens packaged separately by sealing with the cover and placed in their respective boxes.…”
Section: Methodsmentioning
confidence: 99%
“…These standards were used for identification of compounds and analytical method validation purposes, presented in a previous publication [21]. Additionally, a point calibration standard curve (0.01-1 ppm) was prepared and analysed with every run of specimens for quality control purposes Analysis of specimens was conducted per Maitre et al [21]. The method was validated using the ICH Guidelines [26], and found fit for OGSR qualitative analysis purposes.…”
Section: Analytical Method: Ogsr Standards and Uplc-qqq-ms Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies addressing the transfer and persistence of trace materials have developed since the early work of Pounds and Smalldon () (fibers), Brewster, Thorpe, Gettinby, and Caddy () and Hicks, Vanina, and Margot () (glass), and Morgan et al () and Bull, Morgan, Sagovsky, and Hughes () (general particulates). There is now a growing body of published work that addresses a wide range of different physical traces (Bitter, (smoke residues), Maitre et al, (GSRs), Palmer, Sheridan, Puckett, Richardson, & Lo, and Slot et al, (fibers), Levin, Morgan, Scott, & Jones, (diatoms), Morgan, Scott, Ainley, & Bull, (soils) Morgan, Flynn, et al, , and Morgan, Allen, King, & Bull, (pollen)).…”
Section: Understanding Trace Materialsmentioning
confidence: 99%
“…Thus, very sensitive analytical techniques are required. Recent OGSR forensic studies utilizing LC-MS analysis have demonstrated the detection of OGSR on the hands of a shooter up to four hours after discharge [28] and highlighted secondary transfer in several scenarios [29,30]. Currently, OGSR can be detected at the sub-picogram level, due to major improvements in MS sensitivities in the last decade.…”
Section: Introductionmentioning
confidence: 99%